Pursuing Peace through Moral Messages of Jihad: A Way Forward against Misconceptions of Virtual Jihad - Ahmad Faozan (Sunan Kalijaga: International Journal of Islamic Civilization, 2020)
The term ‘jihad’ seems to sound horrible to a number of people. The misunderstood terms and practices apparently continue to rise. Nowadays, the so-called ‘virtual jihad’--as clearly stated in The Sunday Guardian Live, Scientific American, Science Direct, etc.--is addressed as referring to a single connotative meaning of violence in Islam. It seems that they conflate the terms ‘jihad’ and ‘terrorism’. This misunderstood concepts of jihad leads to some acts contradicting the true meaning of ‘jihad’ itself. This article attempts to (1) scrutinize misconceptions of ‘virtual jihad’, (2) delve deeper into the moral principle of jihad due to ideal Islamic teachings, as well as (3) ways forward to put into practice of a “peaceful jihad” in a virtual age. Theoretical Approach used in this study mainly employs Teu Van Dijk’s Critical Discourse Analysis (CDA) models of interrelated texts, social cognition, and social contexts. The findings reveal that (1) misconceptions of ‘virtual jihad’ result from a misunderstood concept of ‘jihad’ itself and underlying ideological factors in the view of Van Dijk’s CDA’s texts, social cognition, and social contexts, (2) fundamentally, the moral concept of jihad is to make meritorious struggle in the cause Allah to do good works and repel evil, as well as to reform a civilized society, and (3) the best practices of jihad in this virtual age is supposed to manifest in the enormous efforts of creating “Knowledge Societies” all the way through the advance of digital technologies. As a final point, it is worth highlighting the importance of being critical, as CDA implies, through the lens of objectivity of any deception, propaganda and biased judgment in this disinformation age as well as generating better solutions for peaceful digital societies.